Biomark J 2019
DOI: 10.36648/2472-1646.5.2.60
|View full text |Cite
|
Sign up to set email alerts
|

Bioinformatics Analysis of Differentially Expressed Genes and Their Functional Enrichment in Acute Myeloid Leukemia Bearing MLL Translocation

Abstract: Background: Chromosomal translocations of the mixed-lineage leukemia gene (MLL; tMLL) correlate with resistance to therapy and an extremely poor prognosis for individuals with Acute Myeloid Leukemia (AML). The underlying mechanisms are still unknown. This study aims to identify the key genes and the potential molecular mechanisms involved in MLL rearrangement in AML using a bioinformatics approach. Methods:The gene expression profiles from 15 individuals with partial tandem duplication of the MLL gene (MLL-PTD… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 45 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…They analyzed the transcriptional profiling of human T-cell involved in the AML disease and reported CD4, NA, ADTRP genes as a diagnostic and therapeutic biomarker. Tang et al (2019) reported the five key genes: ACTR2, ARPC3, ARPC5, CTTN, and APP may be implicated in tumor progression and could potentially represent promising prognostic biomarkers and therapeutic targets for AML biomarker identification in leukemia. There are many studies that have been reported (Prada et al, 2017, Jiang et al, 2016, Sweet et al, 2013 for the identification and characterization of biomarkers for individual classes of leukemia, but the present study was carried out for the comparative analysis of biomarker profiling of major classes (AML, ALL, CML, and CLL) of leukemia.…”
Section: Discussionmentioning
confidence: 99%
“…They analyzed the transcriptional profiling of human T-cell involved in the AML disease and reported CD4, NA, ADTRP genes as a diagnostic and therapeutic biomarker. Tang et al (2019) reported the five key genes: ACTR2, ARPC3, ARPC5, CTTN, and APP may be implicated in tumor progression and could potentially represent promising prognostic biomarkers and therapeutic targets for AML biomarker identification in leukemia. There are many studies that have been reported (Prada et al, 2017, Jiang et al, 2016, Sweet et al, 2013 for the identification and characterization of biomarkers for individual classes of leukemia, but the present study was carried out for the comparative analysis of biomarker profiling of major classes (AML, ALL, CML, and CLL) of leukemia.…”
Section: Discussionmentioning
confidence: 99%